Identifikasi Pemahaman Tentang Konsep Elastisitas Pada Siswa SMPN 7 Toli-Toli - Raja Bone (Jurnal Kreatif Online, 2022)
This study aims to identify students' understanding of the concept of material elasticity after offline learning. The method used is descriptive research with a qualitative approach. The subjects in this study were 17 students of SMPN 7 Toli-Toli class VIII who had attended material elasticity through learning. Respondents who were involved in obtaining data were 3 students selected from each level of student ability, namely high, medium, and low. Based on the results of the study it can be concluded that students' understanding of the concept of elasticity for respondents in the high category is sufficient to understand the concept, medium category respondents still do not understand the concept, and respondents in the low category still do not understand the concept very well.